Cirurgia endoscópica transluminal por orifícios naturais: realidade atual - Santos Filho,Paulo Vicente dos (2009)
Natural orifice transluminal endoscopic surgery (NOTES) is an emerging experimental alternative to conventional surgery that eliminates abdominal incisions and incision-related complications by combining endoscopic and laparoscopic techniques to diagnose and treat abdominal pathology. Natural orifice transluminal endoscopic surgery refers to the method of accessing the abdominal cavity through a natural orifice under endoscopic visualization. Since its introduction in 2004, numerous reports have been published describing different surgical interventions. Recently, a group of expert laparoscopic surgeons and endoscopists outlined the limitations of this approach and issued recommendations for progress toward human trials. Transluminal surgery is a new method for accessing the abdomen under direct endoscopic visualization. Preliminary studies have demonstrated the feasibility of this technique in animal models; however, further research is warranted to validate its safety in humans.